THE IMPACT OF PANIC BUYING ON THE SOCIAL STRUCTURE OF SOCIETY: A STUDY OF THE FUEL CRISIS IN WEST ACEH, INDONESIA - Nesriani; Afrizal Tjoetra; Haliza Abdul Rahman (Program Studi Sosiologi Universitas Malikussaleh, 2026)
This research aims to examine the extent to which panic buying fuel during the crisis in West Aceh affected community social solidarity. This study employs a qualitative method with a descriptive approach. Data was collected through primary observation at fuel stations in Meulaboh City, West Aceh, as well as through literature studies from books, scientific journals, research reports, and documents related to energy crises and community social behavior. Data analysis utilized Emile Durkheim's theory of social solidarity. The research findings indicate that panic buying of fuel weakens mechanical social solidarity due to the emergence of individualistic attitudes, distrust, and competition among residents. However, on the other hand, this crisis also fosters organic solidarity through cooperation and mutual assistance among residents in obtaining fuel and seeking joint solutions. Fuel scarcity can be addressed in various ways, one of which is by optimizing village funds. Village funds can be used to build small-scale pyrolysis facilities that will convert local plastic waste into economically valuable materials. The successful implementation of plastic pyrolysis technology as a long-term solution depends heavily on three main pillars. First, community education and training to ensure proper technology management. Second, infrastructure and funding utilizing village funds to establish communally managed facilities. Third, outreach and government support from the regional to national levels to encourage project adoption and sustainability.